ANALISIS PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN (Studi Pada Perumahan Komplek Amd Permai Banjarmasin) - Risnawati; Nuril Huda (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
The research aims to find out and analyze the effect of product quality and service quality towards consumer’s satisfaction. This research technique is using purposive sampling, as a sampel is inhabitant in residence of perumahan komplek AMD Permai Banjarmasin which is analyze using doubled regretion. The research shows that product quality plays quite a significant role towards consumer’s satisfaction. Service quality affects consumer’s satisfaction significant. And both product quality and service quality affects consumer’s satisfaction significant.